2018
DOI: 10.1371/journal.pone.0193902
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Four-Hour Rule in Western Australian hospitals: Trend analysis of a large record linkage study 2002-2013

Abstract: BackgroundIn 2009, the Western Australian (WA) Government introduced the Four-Hour Rule (FHR) program. The policy stated that most patients presenting to Emergency Departments (EDs) were to be seen and either admitted, transferred, or discharged within 4 hours. This study utilised de-identified data from five participating hospitals, before and after FHR implementation, to assess the impact of the FHR on several areas of ED functioning.MethodsA state (WA) population-based intervention study design, using longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 29 publications
(34 reference statements)
2
49
0
Order By: Relevance
“…Previous research has reported benefits and disadvantages of introduction and assimilation of time‐based targets in ED . Our findings have confirmed that change in management practices was necessary at the introduction and during implementation of the policy, because the majority of the Policy‐associated changes required an oversight of the whole hospital, not just the ED.…”
Section: Discussionsupporting
confidence: 80%
“…Previous research has reported benefits and disadvantages of introduction and assimilation of time‐based targets in ED . Our findings have confirmed that change in management practices was necessary at the introduction and during implementation of the policy, because the majority of the Policy‐associated changes required an oversight of the whole hospital, not just the ED.…”
Section: Discussionsupporting
confidence: 80%
“…Faced with ever-increasing cost constraints as well as demands for services, hospitals have experienced accelerating pressures to step up the pace [6, 13]. For example, time-based targets, such as the rule in Emergency Departments in the United Kingdom and Australia that people need to be seen within four hours [14, 15] and throughput pressures exemplified by elective surgery wait lists [16, 17] are pushing staff to fit more and more tasks into a set amount of time. Work is expanding in other ways too, such as with the introduction of burdensome documentation, rules and regulations [18].…”
Section: Introductionmentioning
confidence: 99%
“…This is a recommended statistical technique for time-trend analysis of populationwide interventions. 4 The impact of NEAT on the outcome measures was assessed statistically with period (pre/post) and calendar quarters as the explanatory variables in the segmented regression model (Appendix S1).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] The National Emergency Access Target (NEAT) policy was implemented in January 2012 by the Australian government to increase ED flow. 4 The aim of this study is to assess changes in time-based measures as proxies for ED crowding and access block before and after NEAT in New South Wales (NSW), Australian Capital Territory (ACT) and Queensland (QLD). [15][16][17] In the UK, at its zenith, 98% of all patients left EDs within 4 h. 15 New Zealand also improved with most district health boards reaching their 95% 6 h target.…”
mentioning
confidence: 99%